Interior design master class : 100 lessons from America's finest designers on the art of decoration - Dellatore, Carl J. (New York, NY : Rizzoli International Publications, Inc., 2016)
"Poised to become the essential reference book on design, Interior Design Master Class features 100 essays by America's top designers -- from established design legends to members of the new guard -- each sharing his or her passion for a single subject. Collectively their expertise and knowledge constitute a complete education in interior design. Grouped by theme...[e]ach piece is paired with images of the designer's work to illustrate the principles being discussed, adding a powerful visual component to the book."--Page 2 of cover.
Theory -- Structure -- Style -- Process -- Elements -- Inspiration.
First published in the United States in 2016.
Includes index and photography credits.
Keywords: Interior decoration; Decoration and ornament; House furnishings; Print books